PENERAPAN METODE GUIDE NOTE TAKING DALAM MENULIS TEKS PROSEDUR PADA SISWA KELAS XI - Sandi Rizky Setiawan; Nia Ariyanti; Rochmat Tri Sudrajat (IKIP Siliwangi, 2019)
This study aims to determine the writing ability of class XI students in learning to write text procedures by applying the Guide Note Taking method. Based on the observations of researchers during the research in class XI, students encounter difficulties in writing procedure texts. In learning writing skills, teachers should use many variations of teaching. One method that can be used as a learning variation is Guide Note Taking. This study uses quasi-experimental research methods, namely quasi-experimental research methods that aim to determine the effect of independent variables on the dependent variable. The data source for the XI grade students in even semester 2018/2019 uses the initial test question sheet, and the final test question sheet. Based on the results of the study of data processing the ability to write text procedures before using the Guide Note Taking method, the initial test (pretest) value of 55.49 after using the Guide Note Taking method obtained the final test score (posttest) of 75.29 . The results of writing ability increased by 19.80. So the hypothesis is accepted. So, it can be concluded that the application of the Guide Note Taking method to learning procedure text writing has been able to improve the results of student learning.